Darul Islam Di Surakarta: Studi Kasus Pemberontakan DI/TII Eks-Batalion 426 Dan Pengaruhnya Tahun 1951-1952 - Nugroho, Agung (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2020)
This study is a study of local history that reconstructs the DI / TII rebellion in the Surakarta Residency in 1951-1952. This rebellion was related to Darul Islam in Central Java targeted the Diponegoro Division of the former Surakarta Hizbullah, namely Battalion 426. This research uses historical methodology through four main stages of the historical method, namely: (1) heuristics, (2) source criticism, (3), interpretation, and (4) historiography. The results of this study indicate that the 426 Battalion came from former Hizbullah Surakarta fighters during the independence war named Hizbullah Sunan Bonang. The DI / TII infiltration was led by Captain Sofyan who had connections with Darul Islam in Central Java. The rebellion lasted for five months from December 1951 to April 1952 dengan Surakarta as the destination. The rebellion was framed with propaganda defending Islam and anti-communism for support. The rebellion influences security stability, its presence is used by local rioters to increase crime, cause economic losses, disrupt transportation, and result in social tension due to the arrest of Muslim communities and local Islamic leaders.